Brucellosis in cattle and buffalo in southern Italian provinces: trends in presence of territory-specific One Health measures - Mazzeo, Alessandra; Mascolo, Celestina; Maiuro, Lucia; Esposito, Marco; Ferrara, Carlo; Rossi, Nicola; Di Chiro, Vincenzo; Rosati, Sebastiano; Sorrentino, Elena (Frontiers in Microbiology, 2025)
IntroductionBrucella spp. infections in livestock continue to pose significant threats to public and animal health, as well as to local economies. In the European Union, Brucella abortus, which primarily affects cattle and buffaloes, has been successfully eradicated in some Member States and across northern and central Italy through mandatory eradication and control programmes. However, some provinces in southern Italy, including Caserta and Salerno (Campania Region), remain affected, while in other provinces, as in Isernia (Molise Region), brucellosis has temporarily re-emerged.MethodsThe study examines brucellosis outbreaks occurring between 2019 and 2023 in these territories, focusing on livestock that play a key role in the milk value chain, an essential pillar for economic sustainability, environmental protection and cultural heritage preservation. Since brucellosis is a WOAH Listed Disease subject to mandatory notification, we analyzed data registered in Italian, European Union and International portals concerning these notifications. Furthermore, we correlated these data to the national and regional rules adopted in order to tackle bovine brucellosis, including the methods approved for the serological diagnosis of infection.ResultsIn Isernia, a mountainous area where cattle ranching and traditional herding are widespread and culturally significant, brucellosis re-emerged in the period 2019–2021, when 30 outbreaks arose, 50% of outbreaks were linked to grazing practices. Outbreaks were promptly extinguished through veterinary intervention due to the low density of farms, which typically house only a few animals, and new cases have not been detected since 2022. The provinces of Caserta and Salerno present a different scenario, as they are major hubs for water buffalo breeding. The stringent tailored control measures, implemented in these provinces through a regional programme, led to a gradual decline in the prevalence of buffalo brucellosis outbreaks in Caserta, that involved 8,766 heads in 2019 and 6,164 heads in 2023, and in the eradication in Salerno, with 369 positive heads in 2019 brought to 0 since 2022. The Caserta programme specifically addresses the province’s particular vulnerabilities, which include frequent flooding events and the presence of the largest and most densely concentrated water buffalo population in Italy.DiscussionThe results highlight the fundamental importance of a One Health approach, which includes targeted interventions adapted to the specific context in which they are applied. This approach must actively involve key stakeholders, including farmers, researchers, public health authorities, and policymakers, and be supported by financial investments. Key components include strengthening biosecurity measures, implementing advanced animal traceability systems, continuous professional training programmes (including for farmers), expert-led information-sharing technologies, and promoting voluntary serological self-monitoring practices.